Brain structure and function differences across varying levels of endurance training: a cross-sectional study - Keying Zhang; Chunmei Cao; Yaxue Wang; Dong Zhang (Frontiers in Human Neuroscience)
BackgroundAlthough previous studies have shown that athletes engaged in endurance sports exhibit unique characteristics of brain plasticity, there has been no systematic investigation into the structural and functional brain characteristics of endurance athletes with varying training levels.MethodsUtilizing the “expert-novice paradigm” design, we employed functional magnetic resonance imaging (fMRI) to obtain images of brain structure and functional activity. We compared differences in gray matter volume (GMV), fractional amplitude of low-frequency fluctuations (fALFF), and degree centrality (DC) among high-level endurance athletes, moderate-level endurance athletes, and non-athlete controls.Results(1) High-level endurance athletes exhibited significantly greater GMV in the left parahippocampal gyrus, bilateral thalamus, right temporal lobe, and bilateral cerebellum compared to both moderate-level endurance athletes and controls. The GMV in these regions showed an increasing trend with more years of endurance training and higher endurance capacity. Additionally, these athletes had significantly higher fALFF in the left superior medial frontal gyrus and right precuneus, as well as higher DC in the right lateral occipital lobe compared to moderate-level endurance athletes. They also had significantly higher DC in the right precuneus and cerebellum compared to the control group. (2) Moderate-level endurance athletes demonstrated significantly greater GMV in the right prefrontal cortex, bilateral medial frontal lobe, right temporal pole, right striatum, and bilateral insula compared to high-level endurance athletes. They also had significantly higher fALFF in the left posterior cingulate gyrus compared to high-level endurance athletes. (3) Control group showed significantly greater GMV in the right amygdala, higher fALFF in the left medial frontal lobe, and greater DC in the left lateral occipital lobe compared to moderate-level endurance athletes.ConclusionAdaptive benefits exhibit different characteristics across different endurance levels. High-level endurance athletes exhibit pronounced enhancements in gray matter volume and functional activity in regions associated with memory, motor control, and sensory processing. While moderate-level athletes demonstrate distinct functional reorganization in the default mode network and cerebellum.